Variation in political metaphor - Thibodeau, Paul H.; Perrez, Julien; Reuchamps, Min (Discourse Approaches to Politics, Society and Culture,, 2019)
"The objective of this book is to understand variation in political metaphor. Political metaphors are distinctive and important because they are used to achieve political goals: to persuade, to shape expectations, to realize specific objectives and actions. The analyses in the book go beyond the mere identification of conceptual metaphors in discourse to show how political metaphors function in the real world. It starts from the finding that the same conceptual domains are used to characterize politics, political entities and political issues. Yet, the specific metaphors used to describe these conceptual domains often change. This book explores some of the reasons for this variation, including features of political leaders (e.g., their age and gender), countries, and other sociopolitical circumstances. This perspective yields a better understanding of role(s) of metaphors in political discourse"--